A Study On View Point Of Chartered Accountants On Gst - Jadav, Jayendrasinh R.; Swadia, Bhavik (International Journal of Psychosocial Rehabilitation, 2020)
Indirect taxes are levied upon goods and services by the central and state governments in India. GST aims to consolidate the entire gamut of these taxes under a seamless Input Tax Credit (ITC - on goods as well as services). By doing so, VAT for the sake of excise duty, special additional duty, and service tax will be canceled. Further, some of these would be included in the GST. With this in mind, GST shall be divided into three categories: central taxes, such as CGST (Central GST), SGST (State GST), and IGST (Integrated GST). Herein, excise duty shall be clubbed with CGST. VAT shall go in the category of state tax, viz. SGST. The foundational core strength of any economy is its financial services industry (including special financial institutions or SFIs, such as banks and NBFCs). Being the economy drivers, these SFIs contribute approximately 6% to the indirect taxes. The implementation and adoption of GST offers a myriad of challenges and avenues for the Indian economy and the industries. This study has been emphasized on to study the view point of chartered accountants on GST.